2006
DOI: 10.1115/1.2349535
|View full text |Cite
|
Sign up to set email alerts
|

Biosyngas Utilization in Solid Oxide Fuel Cells With Ni∕GDC Anodes

Abstract: The combination of biomass gasification systems with fuel cells promises adequate systems for sustainable, decentralized energy conversion. Especially high temperature fuel cells are suited for this task because of their higher tolerance to impurities, their internal steam reforming potential, and favorable thermal integration possibilities. This paper presents the results of biosyngas utilization in solid oxide fuel cells with Ni∕GDC anodes at 850 and 920°C. The relation between the fuel composition and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 7 publications
3
53
3
Order By: Relevance
“…In fact, such a possibility was suggested in early studies. 16 This result also agrees well with the results from current-voltage measurements carried out on a complete cell with Ni/GDC anode, reported elsewhere by the same authors, 17 in which no impact of H 2 S addition was observed on hydrogen oxidation for up to 9 ppm of H 2 S in the feed gas.…”
Section: B26supporting
confidence: 82%
“…In fact, such a possibility was suggested in early studies. 16 This result also agrees well with the results from current-voltage measurements carried out on a complete cell with Ni/GDC anode, reported elsewhere by the same authors, 17 in which no impact of H 2 S addition was observed on hydrogen oxidation for up to 9 ppm of H 2 S in the feed gas.…”
Section: B26supporting
confidence: 82%
“…[1][2][3][4][5][6][7][8][9] The objective of the work reported in this paper is to evaluate the impedance spectra recorded on symmetrical test cells with nickel/ gadolinia-doped ceria ͑Ni/GDC͒ electrodes to understand the influence of gas-phase processes on electrode performance. It is intended that once the arcs due to gas-phase processes in the spectra are identified, the rest of the spectra can be analyzed to study the influence of fuel gas composition or contaminants present in it on the electrode.…”
mentioning
confidence: 99%
“…No relevant data is available about stack performance using biosyngas. Some reports on cell performance using bio-syngas are available [1,19]. Based on these reports, data necessary for system calculations have been assumed.…”
Section: Solid Oxide Fuel Cell Systemmentioning
confidence: 99%